AI-ASSISTED POST-PROCESSING IN CREATIVE PHOTOGRAPHY - Saraswat, Vivek; Mitra, Bhaskar; Das, Omprakash; Ramakrishnan, Udaya; Panigrahy, Abhijeet; Chavan, Pranali (ShodhKosh: Journal of Visual and Performing Arts, 2025)
AI-assisted post-processing has become a revolutionary paradigm in creative photography and changed the way photographers augment, interpret, and convey visual stories. Older post-processing processes are based on extensive use of manual manipulation and pre-processing filters that do not necessarily require technical skills and can require significant amounts of time to execute and are less flexible to the creative intentions of individuals. Recent developments in artificial intelligence, especially in machine learning and deep learning, permit smart and context-dependent post-processing systems that contribute to human creativity but will not substitute it. The paper describes the concept of AI-assisted post-processing as a co-creative model where photographers and intelligent models are engaged in refining images together and enhancing them by refining sharpness, color, tonal arrangement, and artistic processing. The study outlines a conceptual paradigm of human-AI interaction, automation degree, and preservation of a creative intent to make sure that AI interventions are still intelligible and aligned with the artistic vision. The AI methods are discussed, such as neural denoising, super-resolution, HDR reconstruction, neural color grading, and style transfer models with the focus on photographic aesthetics. The article talks about a modular system design, with preparation of datasets, feature extraction in the domains of color, texture, lighting and composition, and the training and inference pipelines, which will be useful to deploy in practice. Evaluation techniques combine both quantitative metrics of image quality and qualitative aesthetic metrics and user studies of photographers and visual artists. The results point to the fact that AI-assisted post-processing can make the work much more efficient, consistent, and creatively explored, and at the same time, preserve author control.